Association between Maternal Anaemia and Postpartum Depression in an Urban Sample of Pregnant Women in Iran (Journal of Health, Population and Nutrition, 2013)
The aim of this prospective study was to determine the relationship between anaemia during pregnancy and postpartum depression. Two hundred eighty-one non-anaemic mothers with singleton and low-risk pregnancy and no history of antidepressant-use were studied. Demographic and reproductive data at week 20 were obtained. Mothers were followed up and haemoglobin (Hb) was checked at delivery. Iranian version of Edinburgh Postpartum Depression Scale (EPDS) was completed 4-6 weeks after delivery. Mean age of the mothers was 26.6}4 years. The prevalence of postpartum depression according to EPDS was 5.5%. Binary logistic regression analysis showed that Hb